Experience in the management of patients with nasal fractures. - Sahily Espino Otero; Julio Romero Rodrígez; Odalys Acevedo Sierra; Jorge Luis Estepa Pérez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: Nasal fracture is the most frequent facial trauma; its immediate treatment help avoiding further complications. Objective: to characterize the patients with nasal fracture who meet the criteria for treatment. Method: An observational, descriptive study was developed, including all patients (114) of 15 years or more with nasal fracture received at the Emergency Maxilo-Facial Surgical Department in the provincial hospital of Cienfuegos from June 2006 to April 2007. The studies variables were age, sex, aetiology, clinical signs, classification depending on the fractures focus and direction of the trauma, treatment following the guidelines for good clinical practices and post-treatment assessment. Results: There was higher incidence of males and the age group between 15 and 44. The main cause of fracture were fights, the most frequent clinical sign was epistaxis. The most common fractures were closed fractures and lateral deviation fractures. Most of the patients received immediate treatment. Among the clinical postsurgical sing was nasal congestion. Conclusions: We proved that immediate care should be provided to patients with this kind of fractures with local anaesthesia to avoid further risks.